Communication Strategies as Catalysts for Enhanced Rice Farming in Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
Rice is one of the most consumed staple foods in the world. It is cultivated in almost every country at both commercial and subsistence levels mostly at the rural agrarian areas. However, production of rice in Nigeria is relatively low and unable to meet local consumption thereby resulting in high importation of the produce to augment domestic needs. One of the major reasons identified as being responsible for the low production of the local rice is lack of information on modern farming methods. This paper focuses on communication strategies as catalysts to communicate information on modern farming practices to boost local rice production in Nigeria. It is a review work based on secondary data and the theoretical framework is premised on diffusion of innovation theory which describes how innovations are communicated through certain channels over a period of time among members of a social system. The paper reveals that access to adequate information on modern agricultural practices helps in knowledge acquisition, enhances production and guarantees food security. It is recommended that policy initiators and change agents should deploy effective communication strategies that would elicit rice farmers’ acceptance, adoption and sustenance of innovations to enhance their production capacities to meet demands.